Minimum tip conical metallized optical fiber probe suitable for scanning probe microscope and preparation method of extremely small tip conical metallized optical fiber probe
Through the method of hot melt stretching and hydrofluoric acid etching modification, a conical metal-plated fiber probe with a curvature diameter of less than 10 nanometers was prepared, which solved the problem that existing probes could not achieve strong coupling at room temperature, and achieved The strong coupling effect between light and substances at room temperature.
Patent Information
- Application Number
- CN202411650560.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
The needle tip curvature diameter of existing scanning probe microscope probes is difficult to reach the nanoscale, and it is impossible to achieve strong coupling between light and matter at room temperature.
The extremely small tip conical metal fiber probe is prepared by thermal melt stretching and hydrofluoric acid etching modification. By first deposition of chromium as a transition layer, the roughness of the subsequent deposition of silver film is improved, and the needle tip curvature diameter is obtained. .
The strong coupling effect between light and matter at room temperature is achieved. The needle tip curvature diameter of the probe is less than 10 nanometers, which is suitable for building a plasmon nano cavity and enhancing the electric field enhancement effect.
Smart Images

Figure CN119470976A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of scanning probe microscopes, in particular to an extremely small tip tapered metal-plated optical fiber probe suitable for scanning probe microscopes and a preparation method thereof. Background Art
[0002] The environment experienced by the material placed in the optical nanocavity will affect its coupling mode with the surrounding light field. Under weak coupling, the atoms in the excited state can radiate photons outward through the spontaneous radiation process. The radiated photons can be reflected by the resonant cavity and may be reabsorbed by the atoms, so the two produce energy exchange through coupling. When the energy exchange rate (i.e., the coupling intensity g) is less than the system energy loss rate (i.e., the cavity loss κ or the relaxation of the atom itself γ), it means that the irreversible photon loss process is dominant, so the atomic radiation process is irreversible. At this time, the radiation properties of the atoms do not change, but their radiation rate can be promoted or suppressed by the cavity, such as chiral Raman spectroscopy and Purcell enhancement; on the contrary, when the coupling intensity is greater than the system loss, that is, when the strong coupling state is reached, light and matter will mix to form a new mixed state, and some interesting quantum plasmon phenomena will be significantly enhanced, such as Rabi splitting, Lamb shift, Stark effect, etc. However, for most optical cavities, the coupling strength g between matter and photons is less than the loss (κ, γ) of the system. To achieve strong coupling in such optical nanocavities, ultra-low temperature, ultra-vacuum and complex construction methods are required to reduce the loss of the system. However, because the coupling strength g between matter and photons is ∝1 / √V, the coupling strength between matter and photons can be enhanced by reducing the volume of the optical nanocavity as an alternative method. Therefore, plasmon cavities with nanoscale mode volumes provide a promising platform for strong coupling systems even at room temperature.
[0003] In recent years, plasmon nanocavities have developed rapidly with the advancement of nanotechnology and have become a research hotspot in the field of nanophotonics. Nanocavity plasmon modes have small mode field volume and high electric field strength, which can enhance the electric near-field-molecule interaction at the nanoscale, such as Purcell enhancement, surface-enhanced Raman scattering and other applications. In addition, because the tip-enhanced nanospectroscopy technology based on scanning probe microscopy (SPM) has sub-nanometer resolution, it provides a powerful platform for accurate identification of physical and chemical phenomena of molecules, such as single-molecule imaging, electrically driven molecular light emission, etc. Therefore, to date, a variety of plasmon probes suitable for scanning probe microscopy have been prepared, including cone-shaped, spiral-shaped all-metal probes, metal nanowires, metal-dielectric composite probes, etc., using more efficient energy coupling methods to achieve stronger electric field enhancement. However, the preparation methods of the above-mentioned probes generally obtain a probe tip curvature diameter of more than 40nm, which makes it difficult for the constructed plasmon nanocavity mode field volume to reach the requirement for achieving strong coupling at room temperature, and it is impossible to further explore the interaction between light and matter. Even though the probe tip curvature diameter can be brought to the atomic level using the technology of modifying atoms at the probe tip, its preparation is too difficult to achieve. Summary of the invention
[0004] In order to solve the shortcomings of the existing probe preparation technology, the present invention proposes a method for preparing a tapered optical fiber probe based on hot melt stretching and hydrofluoric acid etching modification. In order to solve the roughness problem of the silver film deposited by magnetron sputtering, chromium is first deposited as a transition layer to improve the roughness of the subsequently deposited silver film, thereby obtaining a metal-plated optical fiber probe with a smaller needle tip curvature diameter, which can be used to achieve strong coupling between light and matter at room temperature.
[0005] The technical solution of the present invention is:
[0006] A method for preparing a very small tip tapered metal-coated optical fiber probe suitable for scanning probe microscopy, the steps are as follows:
[0007] Step 1: Remove the coating of the single-mode optical fiber, clamp the two ends with an electric translation stage, melt the optical fiber with an oxyhydrogen flame generator, and then use the electric translation stages on both sides to horizontally stretch the optical fiber until it naturally melts to obtain a tapered optical fiber probe;
[0008] Step 2: Arrange the tapered optical fiber probes obtained in step 1 neatly and immerse them vertically in a hydrofluoric acid solution for etching and modification for a certain period of time, then take them out, immerse them in anhydrous ethanol solution to wash away the residual hydrofluoric acid on the surface, and finally place them in a pure environment to dry;
[0009] Step 3: Place a chromium target with a purity of 99.99% and an optical fiber probe into a magnetron sputtering target and a vacuum sample chamber respectively for sputtering deposition. After the sputtering is completed, open the vacuum chamber with nitrogen, replace the chromium target with a silver target with a purity of 99.99%, and perform sputtering deposition again. After the sputtering is completed, open the vacuum chamber with nitrogen, take out the metal-coated optical fiber probe and store it in a pure and dry environment.
[0010] Furthermore, in step 1, the hydrogen in the oxyhydrogen flame generator is cooled by passing through a container filled with a coolant before being used;
[0011] The reaction liquid of the oxyhydrogen flame generator is a potassium hydroxide aqueous solution with a concentration of 15%, and the coolant is an anhydrous ethanol solution.
[0012] Furthermore, the process of generating flame melting and stretching the optical fiber by the oxyhydrogen flame generator in step 1 is divided into two stages. The parameters of the first stage are set as follows: the hydrogen flow rate is 55 SCCM, the initial horizontal stretching velocity of the translation stage is 0 m / s, and the acceleration is 1 m / s 2 After accelerating to 0.2m / s, stretch at a constant speed of 0.2m / s for a period of time until the single-side displacement distance is 0.5cm; the second stage parameters are set as follows: hydrogen flow rate is 48SCCM, the initial horizontal stretching speed of the displacement stage is 5m / s, and the acceleration is -1m / s 2 The unilateral displacement distance is 0.2 cm, and when the unilateral displacement distance of the translation platform reaches 0.2 cm in the second stage, the optical fiber naturally fuses.
[0013] Furthermore, in the flame melting and stretching process of step 1, the curvature diameter of the thin end of the tapered region of the optical fiber obtained in the first stage is 10 μm, and in the second stage, a tapered optical fiber probe is obtained, and the curvature diameter of the needle tip is <5 μm.
[0014] Furthermore, the tapered optical fiber probe prepared in step 1 has a taper angle of 10° and a taper length of 615 μm±30 μm, and the taper angle and the taper length are controlled by parameters in the flame melting and drawing optical fiber process.
[0015] Furthermore, in step 2, the hydrofluoric acid concentration is 40%, the ambient temperature during the etching process is 22° C., the etching time is 3 minutes, the spacing between neatly arranged optical fibers is greater than 0.5 cm, and the angle between the optical fiber and the hydrofluoric acid liquid surface is 90°.
[0016] Furthermore, in step 2, the curvature diameter of the optical fiber probe tip modified with hydrofluoric acid is less than 10 nm.
[0017] Furthermore, in step 3,
[0018] When sputtering chromium target, the magnetron system is evacuated to a vacuum of less than 8×10 -4Pa, argon flow rate 100 SCCM, sputtering power 200 W, coating rate 0.56 nm / s, sputtering time 8 s;
[0019] When sputtering the silver target, the magnetron system was evacuated to a vacuum of less than 8×10 -4 Pa, argon flow rate 100 SCCM, sputtering power 200 W, coating rate 0.83 nm / s, sputtering time 24 s.
[0020] Furthermore, the silver target in step 3 is replaced by a gold target.
[0021] The present invention also provides a very small tip tapered metal-plated optical fiber probe suitable for a scanning probe microscope, which is prepared by the above method.
[0022] The beneficial effects of the present invention are:
[0023] The present invention proposes an extremely small tip tapered metal-coated optical fiber probe suitable for a scanning probe microscope and a preparation method thereof. The tapered optical fiber probe is first obtained by a flame melting taper method, during which the length and the taper angle of the optical fiber taper region can be stably adjusted by changing the flame taper parameters; the optical fiber probes are then batch modified by hydrofluoric acid etching so that the tip curvature diameter is less than 10 nanometers; finally, a chromium thin layer and a silver film are sputtered in sequence by a magnetron method to obtain an extremely small tip tapered metal-coated optical fiber probe.
[0024] Compared with the prior art: (1) The optical fiber probe in the present invention has a very small tip curvature diameter and can be combined with a scanning tunneling microscope to construct a plasma nanocavity mode field volume of 100nm 3 , which is used to achieve strong coupling between light and matter at room temperature; (2) The optical fiber probe in the present invention is prepared by hot-melt taper and hydrofluoric acid etching modification method. The hot-melt taper and etching parameters can be adjusted according to the detection needs to obtain an optical fiber probe with suitable tip diameter, cone angle, and cone area length. The operation is simple and the repeatability is good. It is suitable for a variety of scanning probe microscopes; (3) The optical fiber probe in the present invention is modified by hot-melt taper and hydrofluoric acid etching. While ensuring that the probe is made sharper, chromium is used as a transition layer for depositing a metal film on the probe surface, which improves the adhesion of the subsequently deposited metal to the substrate material, can effectively prevent the metal layer from falling off during use and improve the surface roughness of the metal film.
[0025] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0027] Figure 1 : Flow chart of probe preparation;
[0028] Figure 2 : Comparison of the silver film on the probe surface after direct silver plating and chrome plating followed by silver plating;
[0029] Figure 3 : SEM image of metal-coated optical fiber probe with curvature diameter of 10nm;
[0030] Figure 4 : Fluorescence splitting of R6G800 molecules. DETAILED DESCRIPTION
[0031] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0032] The present invention aims to provide a very small tip tapered metal-coated optical fiber probe suitable for scanning probe microscopy and a preparation method thereof, and the concept is as follows:
[0033] First, a tapered optical fiber probe is prepared by a flame melt stretching method, and then the prepared probe tip is modified by hydrofluoric acid etching. Finally, a thin chromium layer is first deposited on the surface of the optical fiber by magnetron sputtering, and then a metal (gold / silver) layer is deposited on the surface to obtain a sufficiently sharp and smooth dielectric-metal composite optical fiber probe. Combined with a scanning probe microscope system, an extremely small plasmon nanocavity is constructed to achieve strong coupling between light and matter at room temperature.
[0034] Based on this concept, the preparation process of the optical fiber probe with a dielectric-metal composite structure in this example is as follows: Figure 1 As shown, the specific steps are as follows:
[0035] Step 1: Use flame melting to pull the cone, including two electric translation stages, an oxyhydrogen flame generator, and a flow controller. The moving speed, displacement distance, and hydrogen flow rate of the electric translation stage are adjusted by the program to control the cone angle, diameter, and cone length of the tapered optical fiber probe. The specific operations are as follows:
[0036] Remove 2 cm of coating from the single-mode optical fiber, clamp the two ends with an electric translation stage, and melt the optical fiber using an oxyhydrogen flame generator with a 15% potassium hydroxide aqueous solution as the reaction liquid. Then, the optical fiber is stretched horizontally by the electric translation stages on both sides until it melts naturally. The process is divided into two stages:
[0037] The parameters of the first stage are set as follows: hydrogen flow rate is 55 SCCM, initial velocity of horizontal stretching of the translation stage is 0 m / s, and acceleration is 1 m / s 2After accelerating to 0.2 m / s, the fiber was stretched at a constant speed of 0.2 m / s for a period of time until the horizontal stretching displacement distance of the single-side translation stage was 0.5 cm, and the curvature diameter of the thin end of the fiber taper region was 10 μm.
[0038] The parameters of the second stage are set as follows: hydrogen flow rate is 48 SCCM, initial velocity of horizontal stretching of the translation stage is 5 m / s, and acceleration is -1 m / s 2 The displacement distance of the single-sided translation stage is set to 0.2 cm. During this displacement process, the optical fiber naturally fuses, and the obtained tapered optical fiber probe has a cone angle of 10°, a cone zone length of 615μm±30μm, and a needle tip curvature diameter of <5μm.
[0039] In the above process, please note that: the hydrogen in the oxyhydrogen flame generator will be cooled down through a container filled with coolant before use to ensure its safety during storage and use; when using a flow controller, turn on the power, put the valve switch in the closed state first, wait for the gas flow indication on the display to stabilize (normally displayed as zero), then put the valve switch in the valve control state, and adjust the gas flow to the set flow value by setting the potentiometer knob.
[0040] Step 2: The obtained tapered optical fiber is vertically immersed in hydrofluoric acid for a certain period of time for etching and modification, so as to further reduce the curvature radius of the optical fiber probe tip. The specific operation is as follows:
[0041] The tapered optical fiber probes obtained in step 1 are neatly arranged and vertically immersed in a 40% hydrofluoric acid solution for etching and modification for 3 minutes. During the etching and modification process, the ambient temperature is 22°, and the spacing between the neatly arranged optical fibers is greater than 0.5 cm. The optical fiber and the hydrofluoric acid liquid surface are at an angle of 90°. They are then taken out and immersed in an anhydrous ethanol solution for 5 minutes to wash away the residual hydrofluoric acid on the surface. Finally, they are placed in a pure environment to dry. The curvature diameter of the optical fiber probe tip obtained is less than 10 nm.
[0042] Step 3: Place the probe in a magnetron sputtering instrument and deposit chromium first and then silver to obtain a dielectric-metal composite optical fiber probe. The specific operation is as follows:
[0043] The chromium target with a purity of 99.99% and the optical fiber probe were placed in the magnetron sputtering target and vacuum sample chamber respectively. The magnetron system was evacuated to a vacuum of less than 8×10 -4 Pa, argon flow rate 100 SCCM, sputtering power 200 W, coating rate 0.56 nm / s, sputtering time 8 s. After sputtering, the vacuum chamber was opened with nitrogen, the chromium target was replaced with a silver target, and the system was evacuated again to less than 8 × 10 -4Pa, argon flow rate 100 SCCM, sputtering power 200 W, coating rate 0.83 nm / s, sputtering time 24 s. After sputtering, the vacuum chamber was opened with nitrogen, and the metal-coated optical fiber probe was taken out and stored in a pure and dry environment.
[0044] Comparison of the metal film on the probe surface obtained by first depositing chromium and then depositing silver and the traditional direct deposition of silver. Figure 2 As shown, (a) (c) show the silver film on the surface of the optical fiber probe directly plated with silver. It can be clearly seen that the surface silver film exists in discrete islands, it is difficult to form a complete film and the surface is rough. In particular, (c) shows the film at the tip of the probe, where silver aggregated particles can be clearly seen. The size of the particles is uneven and uncontrollable, which will result in that even if the probe tip is extremely small after etching and modification, the particles of silver aggregated at the tip after coating make the final probe tip size larger and difficult to control, which is very unfavorable for the preparation of extremely small tip probes. Through the improved coating method, a thin layer of chrome is first plated and then a silver layer is plated. The silver film on the surface of the optical fiber probe obtained is shown in (b) (d). The surface is very smooth and flat, and very dense. In particular, as shown in (d), the tip of the probe is still a very smooth silver film. Therefore, after we further reduce the size of the tapered optical fiber tip after etching and modification, the dielectric-metal composite probe prepared by this method can reduce the tip curvature diameter to 10nm, as shown in Figure 3 shown.
[0045] The dielectric-metal composite optical fiber probe was fixed on the holder of the scanning tunneling microscope. The constant current mode of the tunneling microscope was used to drive the optical fiber probe to gradually approach the gold single crystal substrate. The current was set to 0.1nA, the bias voltage was +0.1V, and the gain was set to 0.1 to ensure that the gap between the probe and the gold single crystal substrate was stably controlled at 1nm. Then, the concentration was set to 10 -3 mol / L R6G800 fluorescent dye molecules are spread on the surface of a gold single crystal. The scanning tunneling microscope control system is used to slowly move the probe so that the molecule is in the plasma nanocavity constructed by the probe and the gold single crystal. Under the strong coupling between light and molecules, the fluorescence spectrum of the dye molecule is split, such as Figure 4 shown.
[0046] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A method for preparing a very small tip tapered metal-coated optical fiber probe suitable for a scanning probe microscope, characterized in that: Here are the steps: Step 1: Remove the coating of the single-mode optical fiber, clamp the two ends with an electric translation stage, melt the optical fiber with an oxyhydrogen flame generator, and then use the electric translation stages on both sides to horizontally stretch the optical fiber until it naturally melts to obtain a tapered optical fiber probe; Step 2: Arrange the tapered optical fiber probes obtained in step 1 neatly and immerse them vertically in a hydrofluoric acid solution for etching and modification for a certain period of time, then take them out, immerse them in anhydrous ethanol solution to wash away the residual hydrofluoric acid on the surface, and finally place them in a pure environment to dry; Step 3: Place a chromium target with a purity of 99.99% and an optical fiber probe into a magnetron sputtering target and a vacuum sample chamber respectively for sputtering deposition. After the sputtering is completed, open the vacuum chamber with nitrogen, replace the chromium target with a silver target with a purity of 99.99%, and perform sputtering deposition again. After the sputtering is completed, open the vacuum chamber with nitrogen, take out the metal-coated optical fiber probe and store it in a pure and dry environment.
2. A method for preparing a very small tip tapered metal-coated optical fiber probe suitable for a scanning probe microscope according to claim 1, characterized in that: In the step 1, the hydrogen in the oxyhydrogen flame generator is cooled by passing through a container filled with a coolant before being used; The reaction liquid of the oxyhydrogen flame generator is a potassium hydroxide aqueous solution with a concentration of 15%, and the coolant is an anhydrous ethanol solution.
3. The method for preparing a very small tip tapered metal-coated optical fiber probe suitable for a scanning probe microscope according to claim 1, characterized in that: In step 1, the process of generating flames by the oxyhydrogen flame generator to melt and stretch the optical fiber is divided into two stages: The parameters of the first stage are set as follows: hydrogen flow rate is 55 SCCM, initial velocity of horizontal stretching of the translation stage is 0 m / s, and acceleration is 1 m / s 2 After accelerating to 0.2 m / s, run and stretch at a constant speed of 0.2 m / s for a period of time until the single-side displacement distance is 0.5 cm; The parameters of the second stage are set as follows: hydrogen flow rate is 48 SCCM, initial velocity of horizontal stretching of the translation stage is 5 m / s, and acceleration is -1 m / s 2 The unilateral displacement distance is 0.2 cm, and when the unilateral displacement distance of the translation platform reaches 0.2 cm in the second stage, the optical fiber naturally fuses.
4. A method for preparing a very small tip tapered metal-coated optical fiber probe suitable for a scanning probe microscope according to claim 3, characterized in that: In the flame melting and stretching process of step 1, the first stage of the optical fiber tapered region thin end curvature diameter is 10 μm, and the second stage of the tapered optical fiber probe is obtained, and the needle tip curvature diameter is less than 5 μm.
5. A method for preparing a very small tip tapered metal-coated optical fiber probe suitable for a scanning probe microscope according to claim 4, characterized in that: The tapered optical fiber probe prepared in step 1 has a taper angle of 10° and a taper length of 615 μm±30 μm.
6. The method for preparing a very small tip tapered metal-coated optical fiber probe suitable for a scanning probe microscope according to claim 1, characterized in that: In step 2, the hydrofluoric acid concentration is 40%, the ambient temperature during the etching process is 22°, the etching time is 3 minutes, the spacing between neatly arranged optical fibers is greater than 0.5 cm, and the angle between the optical fiber and the hydrofluoric acid liquid surface is 90°.
7. A method for preparing a very small tip tapered metal-coated optical fiber probe suitable for a scanning probe microscope according to claim 6, characterized in that: The curvature diameter of the optical fiber probe tip after hydrofluoric acid modification in step 2 is less than 10 nm.
8. The method for preparing a very small tip tapered metal-coated optical fiber probe suitable for a scanning probe microscope according to claim 1, characterized in that: In step 3, When sputtering chromium target, the magnetron system is evacuated to a vacuum of less than 8×10 -4 Pa, argon flow rate 100 SCCM, sputtering power 200 W, coating rate 0.56 nm / s, sputtering time 8 s; When sputtering the silver target, the magnetron system was evacuated to a vacuum of less than 8×10 -4 Pa, argon flow rate 100 SCCM, sputtering power 200 W, coating rate 0.83 nm / s, sputtering time 24 s.
9. The method for preparing a very small tapered metal-coated optical fiber probe suitable for a scanning probe microscope according to claim 1, characterized in that: The silver target in step 3 was replaced with a gold target.
10. A very small tip tapered metal-coated optical fiber probe suitable for use in a scanning probe microscope, characterized in that: It is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Mach-Zehnder interferometer, and manufacturing equipment and method thereof
CN109000809A
Preparation method of superconductive Josephson probe
CN116981341A
Low-detection-limit DNA sensor and method based on reflective micro-nano biconical optical fiber probe
CN118243635A
Optical fiber nanometer needle tip for near-field optics and preparation method thereof
CN118348282A
Cantilever for Scanning Probe Microscope and Scanning Probe Microscope Equipped With It
US20100154085A1